Growth and Productivity of Different Cultivars of Rice Under Nutrient Expert© and Other Fertilizer Management Practices at Lamjung - Gaire, Achyut; Koirala, Samjhana; Shrestha, Ram Kumar; Amgain, Lal Prasad (International Journal of Applied Sciences and Biotechnology, 2016)
Rice is an important world leading cereal crop grown extensively in tropical and sub-tropical regions of the world. However, its productivity is constrained by a number of problems. Currently, cereal yields are only 40 to 65% of their potential, mostly because nutrient management does not consider crop’s dynamic response to the environment and site specific nutrition management. Therefore, a field experiment was conducted on farmer’s field at Lamjung, Sundarbazar and Bhoteodar using Nutrient Expert® rice model from July 2015 to November 2015. Four replications of 5 treatments were arranged in randomized complete block design. Five treatments were Nutrient Expert recommendation (NE hybrid), Government recommendation (GR hybrid), NE improved, GR improved and Farmers field practice (FFP). The result revealed significant difference in terms of plant height, panicle weight, filled grain/panicle, straw yield, grain yield at 15.5% moisture, biological yield and sterility %.The highest yield (7.362tonha-1) was obtained from NE hybrid field which was followed by GR hybrid (6.12tonha-1), NE improved (5.20tonha-1), FFP (4.76tonha-1) and GR improved (4.70tonha-1). While comparing Nutrient Expert® (NE) estimation for attainable rice yield with actual rice yield from the farmer field trial; NE-based fertilizer recommendations proved to be successful in reaching the yield targets estimated by the software. The actual rice yields recorded in farmer fields were higher than the NE estimated attainable yields, so NE recommendation was found better over GR and FFP. Int J Appl Sci Biotechnol, Vol 4(2): 178-182